Learning Guidance Of Islamic Religious Education In Improving The Implementation Of Worship And Students’ Morals At Elementary School Of Bonto Bontoa, Somba Opu District, Gowa Regency, Indonesia - Mas’ud, Mukhtar; Neti S; Rahman K, Abd.; Dahlan K, Muh. (MSJ : Majority Science Journal, 2024)
This research discusses about Learning Guidance of Islamic Religious Education in Improving the Implementation of Worship and Students’ Morals at Elementary School of Bonto Bontoa, Somba Opu and information from informants qualitatively. This research was carried out at at Elementary School District, Gowa Regency, Indonesia. This study guidance is divided into two implementations, namely the learning guidance in the classroom and outside the classroom. The learning guidance in the classroom includes worship; pillars of Islam, prayer, fasting and alms. Moral learning guidance includes ethics, morality and etiquette for parents, teachers and other people. While the learning guidance outside the classroom includes remedial Islamic religious education (worship material), fast Islamic boarding school and prayer practice. The moral learning guidance includes the materials of students’ morals. This type of research is descriptive qualitative, namely field research which describes the data of Bonto Bontoa, Somba Opu District, Gowa Regency, Indonesia. This research employees a pedagogical approach as the application of educational science or the bases of educational science. The: primary data sources of this research were obtained from Elementary School of Bonto Bontoa, Somba Opu District, Gowa Regency, Indonesia which consists of students, teachers and staff of education. While the secondary data as the supporting one were obtained through studying articles, books written by experts, journals and government publications (laws and government regulations). The results of this research have implications for improving the implementation of worship and the students’ morals of Islamic Religious Education at Elementary School of Bonto Bontoa, Somba Opu District, Gowa Regency, Indonesia, namely: improving the mastery and implementation of worship, such as the ways of performing prayer, fasting, alms and moral. In this case, the students know and practice ethics, morality and attitude towards parents, teachers and can interact well in the community. This is the aim and benefit of learning guidance of Islamic Religious Education.